Assessing of management skills of nursing staff in selected hospitals of Tehran in the evening shift - Baniasad M (Iran University of Medical Sciences, 1988)
EXTRACT  Skillful management role in the success of any profession is clear. Nursing as profession is no exception to this fact. Also nursing mission and role in human life are heavier and require more complex management skills .   Evening and night shift nursing supervisor are employed by a health care institution such as a hospital in the absence of nursing management must have knowledge and expertise in this field . Such as a heart monitor is an essential tool for a nurse in the intensive care unit , management skills are also essential for a nursing supervisor .   When authorities have nursing appropriate management skills , they can achieve the goals of nursing management that have been proposed by Arndt & Huckabay in 1975.